ANALISIS RASIO PAJAK TERHADAP KEBAHAGIAAN DI BEBERAPA NEGARA ASIA-AFRIKA - Yahya Ayasi; Reza Aulia; Marselina Marselina; Vitriyani Tri Purwaningsih; Prayudha Ananta; Rizka Malia (Politeknik Bisnis Indonesia, 2024)
The goal of this research is to examine how income and tax level affect the level of happiness in the nation that make up the Asian-African Conference. Using information from the World Happiness Report's happiness survey as well as tax and income per capita data from the World Bank, OECD, and IMF panel regression data analysis is the technique employed. The Asian-African Conference member nations' happiness index from 2015 to 2023 is the subject of this study. The happiness index is the dependent variable in this study, and the independent variables include tax ratio and income per capita. The study's findings demonstrate that the tax ratio's level significantly affects the happiness index, as well as income per capita. These results obtained a positive influence due to tax management, tax compliance, and income per capita in these countries have been managed quite well.